Stage at diagnosis and survival in patients with cancer and a pre-existing mental illness: a meta-analysis. Issue 1 (25th October 2019) - Davis, Laura E; Bogner, Emma; Coburn, Natalie G; Hanna, Timothy P; Kurdyak, Paul; Groome, Patti A; Mahar, Alyson L
Abstract : Introduction: Individuals with a pre-existing mental illness, especially those experiencing reduced social, occupational and functional capacity, are at risk for cancer care disparities. However, uncertainty surrounding the effect of a mental illness on cancer outcomes exists. Methods: We conducted a systematic review and meta-analysis of observational studies using MEDLINE and PubMed from 1 January 2005 to 1 November 2018. Two reviewers evaluated citations for inclusion. Advanced stage was defined as regional, metastatic or according to a classification system. Cancer survival was defined as time survived from cancer diagnosis. Pooled ORs and HRs were presented. The Newcastle-Ottawa bias risk assessment scale was used. Random-effects models used the Mantel-Haenszel approach and the generic inverse variance method. Heterogeneity assessment was performed using I 2 . Results: 2381 citations were identified; 28 studies were included and 24 contributed to the meta-analysis. Many demonstrated methodological flaws, limiting interpretation and contributing to significant heterogeneity. Data source selection, definitions of a mental illness, outcomes and their measurement, and overadjustment for causal pathway variables influenced effect sizes. Pooled analyses suggested individuals with a pre-existing mental disorder have a higher odds of advanced stage cancer at diagnosis and are at risk of worse cancer survival. Individuals with more severe mental illness, such as schizophrenia, are at a greater risk for cancer disparities. Discussion: This review identified critical gaps in research investigating cancer stage at diagnosis and survival for individuals with pre-existing mental illness. High-quality research is necessary to support quality improvement for the care of psychiatric patients and their families during and following a cancer diagnosis.